Prevalence of Dental Anomalies in Deciduous and Permanent Dentition of Cleft Lip and Palate Patients - Bernardo Olsson; Letícia Fontanella Fernandes; Halina Grossmann Pereira; Beatriz Jervásio Silva; Nicoly Ghilardi Cardoso; Giuseppe Valduga Cruz; Caroline de Souza Mendes; Rafaela Scariot (Pesquisa Brasileira em Odontopediatria e Clínica Integrada)
Objective: To evaluate the association between oral cleft (OC) phenotypes and dental abnormalities (DA) in both permanent and deciduous dentition of patients with Cleft Lip and/or Palate (CL/P). Material and Methods: This cross-sectional study included CL/P patients older than 4 years of age who had orthopantomograms good enough for DA evaluation. The DA evaluated were tooth agenesis, giroversion, root dilaceration, conoidism, fusion, ectopic tooth, concrescence, tooth twinning, and dental transposition. Sample size calculation was performed. The prevalence of DA in deciduous and permanent dentition was reported, both for maxillary and mandibular teeth. Results: A total of 159 patients were included in this study. There was a statistically significant difference in the prevalence of women and men with cleft palate, being cleft palate more prevalent in women (p=0.005). Regarding sexual dimorphism, no statistically significant difference was found between OC phenotypes (p>0.05). Concerning the prevalence of DA in the cleft region, it was observed that DA are more prevalent in permanent dentition (60%) than in deciduous dentition (24%). Conclusion: Oral cleft phenotypes are associated with sex, but dental abnormalities are not, both in permanent and deciduous dentition. The prevalence of dental abnormalities is higher in the cleft region, but mandibular teeth may also be affected. Dental abnormalities in the oral cleft region shows to be more prevalent in permanent dentition than in deciduous dentition.